Toward a technology of treatment individualization for young children with autism spectrum disorders - Stahmer, Aubyn C. (2010)
Although the etiology of autism spectrum disorders (ASD) and early development of the ASD are not yet well understood, recent research in the field of autism has heavily emphasized the importance of early intervention (i.e. treatment before the age of 4 years). Currently, several methods have been demonstrated to be efficacious with some children however no treatment completely ameliorates the symptoms of ASD or works for all children with the disorder. The heterogeneity and developmental nature of the disorder make it unlikely that one specific treatment will be best for all children, or will work for any one child throughout his or her educational career. Thus, this paper examines early research validating different technologies for individualizing treatment. A discussion of current research on pre-treatment characteristics associated with differential outcomes in treatment, including child, family, and practitioner variables; and how specific intervention techniques address each of those pre-treatment characteristics is provided. The ultimate goal of this line of research is to enable practitioners to prospectively tailor treatments to specific children and increase the overall rate of positives outcomes for children with autism. Research that furthers understanding of how to match clients with efficacious treatments will decrease the outcome variability that characterizes early intervention research at present, and provide for the most efficient allocation of resources during the critical early intervention time-period. This type of research is in its infancy, but is imperative if we are to determine a priori which treatment method will be most effective for a specific child.